Heterogeneous Returns to Training: An Analysis with German Data Using Local Instrumental Variables - Anja Kuckulenz; Michael Maier (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
Empirical work on the wage impact of training has noted that unobserved heterogeneity of training participants should play a role. The expected return to training, which partly depends on unobservable characteristics, is likely to be a crucial criterion in the decision to take part in training or not. We try to account for this fact by using recent advances in estimating returns to schooling, which allow for selection on unobservables, and apply it to estimating the impact of training on earnings. Allowing heterogeneity to be unobserved by the econometrician, but assuming that individuals may act upon this heterogeneity, completely changes the interpretation and properties of commonly used estimators. Our results based on local instrumental variables suggest that traditional estimates of the wage impact of training overestimate this effect.
Keywords: J31; C14; C21; 330; Vocational training; treatment effects; semiparametric estimation; Local instrumental variables; Betriebliche Weiterbildung; Bildungsertrag; Instrumentalvariablen-Schätzmethode; Schätzung; Deutschland